Pruning Studies in Ber (Zizyphus mauritiana Lank) Under Dryland Conditions - Chovatia, R S; Patel, D S; Patel, g V; Patel, A T (Annals of Arid Zone, 2016)
The pruning study on Ber Cv. Gola revealed that the pruning at 4th secondary branches gave higher shoot length, fruit set, fruit weight as well as less fruit drop resulting in signiffcantly higher fruit yield. Total soluble solids. acidity and ascorbic acid content were not influnced by the pruning treatments. The dry weight of pruned wood was maximum in pruning at 4th secondary branches.